A study of patient satisfaction after cataract surgery with implantation of different types of intraocular lenses - Wei Ching-Kuo (BMC Research Notes, 2012)
Abstract Background The implementation of capitated payment has driven medical institutions through developing balance billing for medical services. By exploring the patients’ decision-making factors on different self-pay items, a reference for the pricing and sales strategy for the related products can be formed. The major purposes of this study were to analyze the determinants of preoperative selection and postoperative satisfaction with implantation of different types of intraocular lenses in cataract surgery. Methods This cross-sectional study consisted of 127 patients that were 50 years of age and older, and who had phacoemulsification with intraocular lens implantation in both eyes. Data were collected by using a structured questionnaire. The following parameters were measured: access to medical care, attitude towards receiving medical products at one’s own expense, overall patient satisfaction and postoperative visual clarity. Results The results showed that the patient’s gender, educational level and economic status influenced the type of intraocular lens chosen. Patients in the insurance group cared about access to medical care, and patients in the balance billing group cared about product differentiation. ANOVA results showed no statistically significant differences in the overall satisfaction of the patients among the groups with different types of intraocular lenses. Patients that received cataract surgery with implantation of multifocal intraocular lenses had better vision when trying to view smaller objects and when looking at objects under strong light. Conclusions Manufacturers should increase the number of differences between their products, and health care providers can then recommend the appropriate intraocular lens in accordance with the needs or demands of their patients, and also by keeping in mind the financial constraints of their patients.